2009
DOI: 10.53383/100113
|View full text |Cite
|
Sign up to set email alerts
|

International Real Estate Review

Abstract: This paper examines the inflation-hedging behavior of the Hong Kong securitized real estate market between April 1986 and April 2007. The monthly series of the Hang Seng Property Index (HSPI) is selected as the proxy of the Hong Kong securitized real estate market due to its comprehensive coverage and availability of rich data. We find that the vector autoregressive forecast error method, which is introduced by Den Haan (2000), outperforms the traditional linear vector autoregressive model and vector error cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Voigtlander & Demary [21] studied the inflation hedging performance of real estate in Canada, USA, Finland, France, Germany, Ireland, the Netherlands, Sweden and the UK, the authors found that investment in real estate equities did not protect the investors against inflation. Similar tests had been conducted in other developed economies such as: Hong Kong [16, 20,23], Switzerland [24], China [8], Sweden [17] and Korea [9]. All these studies, showed divergent findings with respect to real estates' performance as an inflation-hedge.…”
Section: Literature Reviewmentioning
confidence: 58%
See 1 more Smart Citation
“…Voigtlander & Demary [21] studied the inflation hedging performance of real estate in Canada, USA, Finland, France, Germany, Ireland, the Netherlands, Sweden and the UK, the authors found that investment in real estate equities did not protect the investors against inflation. Similar tests had been conducted in other developed economies such as: Hong Kong [16, 20,23], Switzerland [24], China [8], Sweden [17] and Korea [9]. All these studies, showed divergent findings with respect to real estates' performance as an inflation-hedge.…”
Section: Literature Reviewmentioning
confidence: 58%
“…Payton [4] and Arnasosn & Persson [17] asserted that intuitively, real estate has been perceived to be a good hedge against inflation all over the world. To justify or refute this notion, different studies have been carried out in both developed and developing economies, these studies included: Fama & Schwert [6]; Sing & Low [18]; Bello [7]; Quingping [19]; Liu & Zhou [20]; Voigtlander, & Demary [21]; Ma & Liu [22]; Zhe [16]; Payton [4]; Arnasosn & Persson [17]; Fraundorf [2]; Akinsola [3]; Ogunba, et al [12]; etc. The results obtained from studies conducted in developed economies were observed to be far from having consensus.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This study suggests that further research study can be carried out in comparison with REITs such as that of US REITs [93][94][95]. Another suggestion involves the consideration of different components and characteristics of inflation [49,[96][97][98][99], and then comparing in different countries. This can also involve the inflation hedging portfolio within real estate, such as the Real Estate Securities and Real Estate Investment Funds [100][101][102][103][104][105][106].…”
Section: Inflation-hedging Dynamics Of Real Estate Investment Returnsmentioning
confidence: 99%